Antiviral effects of Atractyloside A on the influenza B virus (Victoria strain) infection - Han, Jicheng; Zhu, Xiangyu; Gao, Zihan; Xiao, Yan; Zhang, Jinxin; Wang, Peng; Fang, Jinbo; Li, Yiquan; Zhu, Yilong; Li, Yue; Jin, Ningyi; Lu, Huijun; et al. (Frontiers in Microbiology, 2023)
Influenza viruses pose a serious threat to human health, infecting hundreds of millions of people worldwide each year, resulting in a significant increase in global morbidity and mortality. Influenza activity declined at the onset of the COVID-19 pandemic, but the genetic diversity of B/Victoria lineage viruses has increased significantly during this period. Therefore, the prevention and treatment of the influenza B Victoria strain virus should still attract extensive attention. In this study, we found that Atractylodes A (AA), one of the effective components in Atractylodes lancea (Thunb.) DC, shows a potential anti-viral infection function. This study shows that AA not only has anti-influenza B virus infection effects in vivo and in vitro, but also can regulate macrophage polarization to the M2 type, which can effectively attenuate the damage caused by influenza B virus infection. Therefore, Atractylodes A may be an effective natural drug against B/Victoria influenza infection.